Online employment portal architecture based on expert system - Priyanka, Janampally Himabindu; Parveen, Nikhat (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Now a days, choosing the skill set which belongs to current marketing trends that suits him/her is difficult especial for the fresher (who is an employee). It is even more complex for the employer to requite the required skilled person. As there will be huge data. To match these two requirements, we need an expert system. An expert system which can cluster the data as well as to answer the query posted by both employee and employer. In this paper, component-based architecture is described which includes cloud computing, the cluster and software agents.